2008
DOI: 10.3340/jkns.2008.43.5.246
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Apoplexy due to Pituitary Adenoma Infarction

Abstract: Pituitary apoplexy is a life-threatening clinical syndrome which is caused by the fulminant expansion of pituitary mass due to hemorrhage, hemorrhagic infarction or infarction of pituitary adenoma or the adjacent tissues of pituitary gland. Since first introduced by Bailey in 1898, the incidence of pituitary apoplexy varies from 0.6% to 22.8% 7,11,12,17) . However, pituitary apoplexy due to tumor infarction is very rare. We report two cases of pituitary apoplexies, caused by pituitary tumor infarction after su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 16 publications
0
26
1
Order By: Relevance
“…Isolated third cranial nerve palsy as the presenting sign of pituitary tumors and Sheehan's syndrome is very rare. Only a few cases of isolated third cranial nerve palsies in patients with pituitary tumors have been previously reported in the literature 4,5,7,14,15) . Previous reports have proposed several mechanisms to explain the occurrence of isolated third cranial nerve palsy in pituitary apoplexy.…”
Section: Discussionmentioning
confidence: 99%
“…Isolated third cranial nerve palsy as the presenting sign of pituitary tumors and Sheehan's syndrome is very rare. Only a few cases of isolated third cranial nerve palsies in patients with pituitary tumors have been previously reported in the literature 4,5,7,14,15) . Previous reports have proposed several mechanisms to explain the occurrence of isolated third cranial nerve palsy in pituitary apoplexy.…”
Section: Discussionmentioning
confidence: 99%
“…Pituitary apoplexy may occur first leading to internal carotid artery occlusion. 5,14) Vasospasm may be caused by extravasation of blood from the pituitary tumor into the subarachnoid space or the vasoactive agent released from the pituitary tumor into the hypophyseal area. 10) We speculate that if the vasoactive agent is the main factor to cause acute internal carotid artery occlusion, the bilateral internal carotid arteries should be occluded.…”
Section: Discussionmentioning
confidence: 99%
“…This result has shown that pituitary adenoma producing internal carotid artery occlusion was extremely rare. In literature review we have found five case reports describing pituitary tumors producing carotid artery occlusion without the presence of apoplectic events (10,(21)(22)(23)(24). Table 1 has summarized the details of these reports.…”
Section: Discussionmentioning
confidence: 99%